Daring greatly : how the courage to be vulnerable transforms the way we live, love, parent, and lead - Brown, Brené (Gotham Books, 2012)
Based on twelve years of research, thought leader Dr. Brené Brown argues that vulnerability is not weakness, but rather our clearest path to courage, engagement, and meaningful connection.